Orthorhombic two-dimensional crystal form of purple membrane. - Michel, H (1980)
A new two-dimensional crystal form of purple membrane has been obtained in vitro. It is produced by the joint use of a cationic detergent, dodecyltrimethylammonium chloride, and the nonionic detergent, Triton X-100. It primarily forms large, rolled-up sheets that look like needles in the light microscope. Liposomes and tubes are also observed. The absorption maximum of the new form of purple membrane is blue-shifted by 6 nm and its density is slightly lower than the natural form of purple membrane. The new form of purple membrane is orthorhombic with space group p22121 and cell dimensions 57.6 x 73.5 A. Four molecules of bacteriorhodopsin occupy the unit cell with an area per molecule close to that found in the native p3 structure. The projected structure to 6.5-A resolution was determined by electron microscopy and diffraction. It shows an identical molecular structure to that of the p3 form and determines the position of the polypeptide boundary.